Paradoks Environment, Social, Governance (ESG): Investigasi Kinerja Perusahaan Berdasarkan Horison Waktu - Dyna Rachmawati; Stefany Hadinata (Politeknik Ganesha Medan, 2026)
This study examines the impact of ESG on performance based on a time horizon. Previous studies have examined the impact of ESG on short-term performance, using ROA as a proxy. This study attempts to fill this research gap by examining the impact of ESG on both short- and long-term performance. This examination of ESG on performance based on a time horizon represents a novelty. This study used a sample of 314 non-financial companies for the period 2021-2024. Hypothesis testing used two-stage least squares to address endogeneity issues. The instrument variables used in this study were company size, leverage, and liquidity. The test results indicate that ESG has a positive impact (no effect) on the sustainable growth rate (SGR) (return on assets/ROA) as a proxy for long-term performance (short-term performance). ESG decomposition does not affect either long- or short-term performance. The good corporate governance index has a positive effect on both long- and short-term performance. The industrial sector does not affect either long- or short-term performance. The results of this study provide practical contributions: first, recognizing that ESG is an investment for companies, so returns take time over the long term. Second, good governance is needed by companies to be able to produce good performance in the long and short term.